2D Motion Analysis of Knee Joint Angulation in Transtibial Amputees Using SACH Foot at Prosthetics and Orthotics Clinic, Polytechnic of Health Jakarta I - Putri, Kinanti Restiana; Hjelmström, Olle; Lestari, Tri Riana; Adyas, Atikah (Poltekkes Kemenkes Jakarta I, 2022)
The neutral foot position of the prosthetic SACH foot has a higher heel surface from the front of the foot (metatarsal line) with 1cm heel height. The prosthesis will be aligned to match the shoes that patient will use. When the patient is using shoes, the prosthetic SACH foot will be placed in a neutral position and will be supported by the shoe. When the patient does not use the shoe, the prosthesis will tilt backward especially when the foot is mid-stance and will force the pressure of the knee toward the extension of the knee joint which can cause damage to the knee joint structure. Therefore, knee joints will be measured at the time of the patient's use and not wearing shoes during mid-stance. Objective: To find out if there are significant differences in knee joint degree during mid-stance when using and not using shoes with 1cm heel height. Methods Quantitative comparative by observation of 2-dimensional motion in transtibial amputation patients using shoes and not using shoes with cross-sectional study design. Result : The degree of knee joints generated during mid-stance by patients with transtibial amputation when using shoes was 10.8o of flexion (p = 0.004) while at the time of not using the resulting knee boots was 4.5o of flexion (p = 0,000), normal degree of knee joint during mid- stance is 10o-20o of flexion. The results of paired t-test showed that there were significant differences in knee joint degree from standard degree, but when using the shoe showed a result of 0.8o larger than the lowest normal range while when not using shoes the resulting degree of 6.3o is smaller than lowest normal range.